Speaking to the people? Money, trust, and central bank legitimacy in the age of quantitative easing - Benjamin Braun (Max Planck Institute for the Study of Societies, 2016)
Financial upheaval and unconventional monetary policies have made money a salient political issue. This provides a rare opportunity to study the under-appreciated role of monetary trust in the politics of central bank legitimacy which, for the first time in decades, appears fragile. While research on central bank communication with "the markets" abounds, little is known about if and how central bankers speak to "the people." A closer look at the issue immediately reveals a paradox: while a central bank's legitimacy hinges on it being perceived as acting in line with the dominant folk theory of money, this theory accords poorly with how money actually works. How central banks cope with this ambiguity depends on the monetary situation. Using the Bundesbank and the European Central Bank as examples, this paper shows that under inflationary macro-economic conditions, central bankers willingly nourished the folk-theoretical notion of money as a quantity under the direct control of the central bank. By contrast, the Bank of England's recent refutation of the folk theory of money suggests that deflationary pressures and rapid monetary expansion have fundamentally altered the politics of monetary trust and central bank legitimacy. – – Die durch die Finanzkrise und die unkonventionellen Maßnahmen der Zentralbanken bewirkte Politisierung des Geldes erlaubt einen seltenen Einblick in den Zusammenhang zwischen Geldvertrauen und Zentralbanklegitimität. Die Kommunikation von Zentralbanken mit der breiten Öffentlichkeit - im Gegensatz zur gut erforschten Kommunikation mit Finanzmärkten bisher weitgehend vernachlässigt - sieht sich mit einem Dilemma konfrontiert. Einerseits hängt die Legitimität der Zentralbank davon ab, ob ihr Handeln den Maximen entspricht, die sich aus der in der Öffentlichkeit vorherrschenden Theorie des Geldes ableiten. Andererseits weicht diese Theorie in wichtigen Punkten von der tatsächlichen Funktionsweise des Geldsystems ab. Wie Zentralbanken mit diesem Dilemma umgehen, hängt von der allgemeinen geldpolitischen Situation ab. Anhand der Beispiele der Deutschen Bundesbank und der Europäischen Zentralbank wird argumentiert, dass Zentralbanker unter inflationären Bedingungen die Öffentlichkeit gerne in dem Glauben lassen, die Geldmenge sei vollständig von der Zentralbank kontrolliert. Die außergewöhnliche Initiative der Bank of England, die Öffentlichkeit von der Irrtümlichkeit dieser Vorstellung zu überzeugen, zeigt hingegen, dass deflationärer Druck und rapide geldpolitische Expansion das diskursive Verhältnis zwischen Geldvertrauen und Zentralbanklegitimität grundlegend verändert haben.
Keywords: 300